Open Approach to Primary Lumbar Hernia Repair: A Lucid Option - Ketan Vagholkar; Suvarna Vagholkar (Case Reports in Surgery)
Background. Lumbar hernia is a rare type of hernia. Awareness of the anatomical basis of this hernia is important for proper diagnosis and treatment. Introduction. Lumbar hernia is a protrusion of either extraperitoneal fat or intraperitoneal contents through either of the lumbar triangles. Primary lumbar hernias are extremely rare thereby rendering such a case reportable, to create an awareness about this condition to upcoming surgeons. Case Report. A case of primary lumbar hernia treated successfully by open mesh repair is presented. Discussion. The anatomical aspects underlying this condition along with diagnostic tests, their pitfalls, and surgical approaches are discussed. Conclusion. Awareness of this condition is essential for arriving at a clinical diagnosis. CT scan provides a road map for deciding the approach. Both the traditional open and the newer laparoscopic approaches are described. However open meshplasty is still a very safe and effective method of treatment.